(untitled) (Argos, 2021)
The development of General Linguistics in recent decades has produced important innovations in the knowledge of the functioning mechanisms of ancient and modern languages. However, these innovations have not yet fully entered the study of the Latin language. In this contribution, examples of application of the so-called “new comparative method” to some traditional problems of Latin grammar are proposed. In particular, the paper presents a description of the structure of the syllable and of the Latin accent law, a proposal for analyzing the structure of morphemes, and an introduction to the phrase structure.